Effect of extended InterTAN intramedullary nail internal fixation on elderly femoral intertrochanteric fractures - CHEN Degao; YE Meng; ZHANG Bao (Zhongguo linchuang yanjiu, 2024)
Objective To explore the effect of extended InterTAN intramedullary nail internal fixation in the treatment of elderly femoral intertrochanteric fractures and its influence on hip function and incidence rates of complications. Methods A total of 138 patients with femoral intertrochanteric fractures aged≥60 years admitted to Orthopedics Department of Anhui Medical University Affiliated Hefei Hospital from April 2019 to May 2022 were included. According to the different intramedullary nails during surgery, the patients were divided into short nail group (n=70, standard InterTAN intramedullary nail) and long nail group (n=68, extended InterTAN intramedullary nail). The perioperative conditions (intraoperative blood loss, surgical time, ambulation time, fracture healing time and the rate of internal fixation failure), complications, visual anologue scale (VAS) scores at 1 day, 3 days, 1 month and 3 months after surgery were compared between the two groups. The patients were followed up for 6 months, and Harris scores were compared between the two groups before surgery and at 3 months and 6 months after surgery. Results Compared with short nail group, intraoperative blood loss was more ［(266.15±52.73) mL vs (243.29±46.13) mL, t=2.71, P=0.01］ and surgery time was longer ［(84.21±14.54) min vs (72.57±13.08) min, t=4.95, P＜0.01］ in long nail group (P＜0.05), but the ambulation time ［(9.32±1.74)d vs (11.50±1.67) d, t=7.51, P＜0.01］ and fracture healing time ［(3.36±1.24) months vs (3.85±1.26)months, t=2.30, P=0.02］ were significantly shorter (P＜0.05). There was no statistically significant difference in internal fixation failure rate and incidence of postoperative complications between two groups (P＞0.05). VAS scores of the two groups was gradually decreased, and the difference was significant at different time points within the groups (P＜0.05). VAS scores in long nail group at 1 day, 3 days, 1 month and 3 months after surgery were significantly lower than those in short nail group (P＜0.05). The Harris scores revealed a statistical difference from the aspects of between-group, time-point and interaction (P＜0.05). The Harris scores in the two groups showed an upward trend, and there was a significant difference at various time points (P＜0.05), and the Harris scores in long nail group at 3 months and 6 months after surgery were significantly higher than those in short nail group (P＜0.05). Conclusion Both standard and extended InterTAN intramedullary nail internal fixation can effectively treat elderly femoral intertrochanteric fractures, but extended InterTAN intramedullary nail has faster healed, milder postoperative pain and better hip function recovery.